2018
DOI: 10.7759/cureus.2911
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Adding Red Cell Distribution Width to Mehran Risk Score to Predict Contrast-induced Acute Kidney Injury in Patients with Acute Coronary Syndrome

Abstract: Background: Contrast-induced acute kidney injury (CI-AKI) is a relatively reversible cause of acute kidney injury (AKI) that occurs after radiocontrast media administration. It is a common complication after percutaneous coronary intervention, especially in patients with acute coronary syndrome (ACS). The aim of this study is to determine the utility of red cell distribution width (RDW) in predicting CI-AKI in patients with ACS and to determine the value of adding RDW to the Mehran risk score (MRS) on admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…According to the inclusion criteria established for the present study, an additional 58 articles were excluded. We thus finally selected 26 studies, 1843 which consisted of a cohort of 29 454 patients receiving coronary intervention (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…According to the inclusion criteria established for the present study, an additional 58 articles were excluded. We thus finally selected 26 studies, 1843 which consisted of a cohort of 29 454 patients receiving coronary intervention (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…included 1251 cases and 1663 controls were identified meeting the criteria for inclusion in our meta-analysis, with publication years ranging from 2015 to 2018 [21,[26][27][28][29][30][31].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The key features of 8 studies on the association between RDW and AKI are shown in Table 1. In those studies, half of which including Caucasian descents (3 published papers included 4 RCSs) [21,26,27] and the other half of which including Asian descents [28][29][30][31]. All the included studies were prospective cohort studies, and the mean age years of the patient with AKI range from 6.7 to 68.9.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All of the 26 selected studies assessed the association analysis between preangiography CRP/hs-CRP, hematological indices and CIN, 13 of them contained the relationship between CIN and CRP/hs-CRP(19, 23, 24, 27, 28, 32, 34-36, 38, 39, 41, 43), while 5 of them reported NLR(25,36,38,39,42), 4 explored PLR(19,26,36,42), 5 RDW(29,30,40,41,44) and 7 HCT…”
mentioning
confidence: 99%